Sebaran Salinitas dan Temperatur Secara Horzontal di Muara Sungai Palu - Sucipto, A.; Thaha, M.A.; Hatta, M.P.; Mahmuddin, F. (Tadulako University, 2024)
Salinity and temperature are easily measured oceanographic factors that play an important role in physical, chemical and biological processes in the ocean. Therefore, information on the distribution of temperature and salinity is very important. Palu River is the main channel that has an important function in flowing the discharge that empties into Palu Bay. The coastal waters around the mouth of Palu River is a potential area for social and economic development of the surrounding community. Dependence on so many important commercial fisheries in the estuarine waters is one of the main economic reasons for conserving this habitat. Based on this, this study was conducted with the aim of determining the distribution of salinity and temperature in the Palu River estuary. Data were collected at 11 observation stations from October 24, 2022 to October 26, 2022, horizontally. The methods used were theoretical approaches and field observations. Data processing used ArcGis 10.8 software and ODV (Ocean Data View) 4.0. The research results from the distribution of salinity at 11 observation stations horizontally ranged from 3.63 to 36.10 ppt, while the temperature ranged from 26.30 °C to 29.30 °C. Salinity and temperature values varied at each depth. It appears that the tides and the flow of river water affect the distribution of salinity and temperature.